(3cJGH GdRjL GdbSjfis - (3Ydj Hf EHQGgje Hf eMeO GdCfUGQj GdehbJ, CHh GdMSf YdGA GdOjf, GdeYQha HGHf GdTGWQ,J (B777 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ gPG gh GdRjL GdbSjfi fRgI ReGfg GdQUO GdLOjO GdeQUhO ai eOjfI HGQjS s
(3BNQgG (B:s
(3HBNQgG LOGhd adcjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eJQLe ef GdaQfSjI Edi GdJQcjI hefgG Edi GdYQHjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B965s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs